2014
DOI: 10.1039/c4cy00613e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Fe additive improving the activity stability of microzeolite-based Mo/HZSM-5 catalyst in non-oxidative methane dehydroaromatization at 1073 K under periodic CH4–H2switching modes

Abstract: ARTICLE This journal isThe catalytic stabilities of Fe-modified and -unmodified 5%Mo/HZSM-5 catalysts in the non-oxidative methane dehydroaromatization were compared at 1073 K and three reaction/H 2 -regeneration cycle periods: 5 min CH 4 -5 min H 2 , 5 min CH 4 -10 min H 2 , and 5 min CH 4 -20 min H 2 . Fe addition proved capable of remarkably increasing the catalyst stability over the cycles of 5 min CH 4 -20 min H 2 but hardly effective over the cycles of 5 min CH 4 -5 min H 2 . On the other hand, SEM obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
3
11
0
Order By: Relevance
“…Summarizing the previous literature results, only the catalytic performance reported by Sun et al [56] and Xu et al [48] (based on the periodic CH 4 -H 2 switching) and that reported by Wang et al [57] (based on the use of hollow ZSM-5 capsules) match the results obtained with the SC-STS-E sample in terms of catalytic stability and aromatics yield. On this regard, the potential advantages of the suggested SC-STS-E method with respect to the synthesis procedures described above are two-fold: i) SC-STS is a continuous synthesis procedure and commercially available ZSM-5 zeolites can be used as catalyst support, i.e.…”
Section: Catalyst Performance Evaluationsupporting
confidence: 80%
See 2 more Smart Citations
“…Summarizing the previous literature results, only the catalytic performance reported by Sun et al [56] and Xu et al [48] (based on the periodic CH 4 -H 2 switching) and that reported by Wang et al [57] (based on the use of hollow ZSM-5 capsules) match the results obtained with the SC-STS-E sample in terms of catalytic stability and aromatics yield. On this regard, the potential advantages of the suggested SC-STS-E method with respect to the synthesis procedures described above are two-fold: i) SC-STS is a continuous synthesis procedure and commercially available ZSM-5 zeolites can be used as catalyst support, i.e.…”
Section: Catalyst Performance Evaluationsupporting
confidence: 80%
“…The increased accessibility of the internal acid sites in the Mo-loaded hierarchical MCM-22 improved benzene selectivity during MDA. Sun et al [56] used a periodic CH 4 -H 2 switch strategy similar to that reported by Xu et al [48] keeping a nearly constant methane conversion (13 -16%) and outstanding aromatics yield (>10%) for 1000 hours on stream, which represents the longest reported TOS in literature for the MDA process. Wang et al [57] synthesized an unconventional hollow ZSM-5 zeolite capsules with large cavity in core and aggregated mesopores in shell that significantly outperformed the conventional ZSM-5 microporous support in terms of methane conversion and aromatics selectivity.…”
Section: Catalyst Performance Evaluationmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhang and co-workers investigated the effect of periodic CH 4 –H 2 switch operation mode in the MDA reaction. Their research was conducted on various catalysts and in different kinds of reactors. , In 2011, Zhang et al carried out a research to study catalytic behaviors of regeneration (CH 4 –H 2 switch) cycles over Mo/HZSM-5 catalyst (5 wt % Mo, Si/Al = 30) in a two-bed circulating fluidized bed system. The reaction occurred at 1073 K with space velocities of 21 080 and 40 000 mL/g h. The results revealed that more than 50 wt % of the coke formed in the initial 2 min of the reaction.…”
Section: Development Of Catalysts For Mdamentioning
confidence: 99%
“…The nonoxidative aromatization of methane over Mo/HZSM‐5 provides a promising route of direct methane conversion to valuable aromatics. It has been extensively studied from both fundamental scientific and application points of view since first reported in 1993 . Since Mo/HZSM‐5 catalyst always shows a very rapid deactivation at severe reaction conditions due to serious coke formation, suppressing coke accumulation and maintaining its high activity has become the key to realizing early industrial application of this new catalytic reaction system .…”
Section: Introductionmentioning
confidence: 99%